Executive Functions and Their Relation to Academic Performance in University Students - Macarena V. del-Valle; Lorena Canet-Juric; Eliana V. Zamora; María L. Andrés; Sebastián Urquijo (Psicología Educativa: Revista de los Psicólogos de la Educación, 2024)

(untitled)
Academic performance, dropout rates, and low graduation rates constitute an area of concern in Latin American universities that has been the topic of various studies. Certain researchers suggest that some differences in academic performance could arise from interindividual variations in self-regulation mechanisms such as executive functions. Therefore, this study aimed to contribute to the investigation of the relationships between university performance and executive functions, specifically working memory, inhibition, and shifting. The study involved 196 students who completed the Reading Span Task, the Five Digits Test, and the Finger Task. Working memory, inhibition, and shifting exhibited a weak significant relationship with performance. Furthermore, additionally to age, socioeconomic status, and student work hours, inhibition and shifting accounted for 38% of the variance in academic performance. The findings provide a contribution to the understanding of this topic and to the discussion of previous contradictory findings.